Perceived Risk Over Halal Awareness: Driving Halal Skincare Purchase Intention Among Gen Z Muslim Women - Ali Imaduddin Futuwwah; Phonny Aditiawan Mulyana; Muhammad Anang Firmansyah (Jurnal Ekonomika dan Bisnis Islam, 2026)
The halal skincare market has expanded significantly, driven by increasing religiosity and heightened consumer concern over product safety among Muslim populations. Despite this growth, scholarly understanding of how halal awareness translates into actual consumer attitudes remains inconsistent across empirical studies. Drawing on the Theory of Planned Behaviour (TPB), this study investigates the roles of halal awareness and perceived risk in forming consumer attitudes and, subsequently, purchase intentions toward halal skincare products. A quantitative approach was employed, with data gathered from 200 Generation Z Muslim female university students using a structured self-administered questionnaire. Hypothesized relationships were evaluated through Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings reveal that halal awareness exerts no significant direct effect on consumer attitudes toward halal skincare, whereas perceived risk demonstrates a significant and positive influence on attitude formation. Furthermore, consumer attitude was confirmed as a significant mediator linking perceived risk to purchase intention. These results suggest that among Gen Z Muslim female consumers, risk-related cognition holds greater behavioral relevance than religious knowledge in cultivating favorable attitudes toward halal skincare. This study advances the halal marketing literature by broadening the TPB framework through the incorporation of perceived risk as a key antecedent, while offering actionable insights for brand managers and marketers operating in the halal cosmetics sector.